Micro-credit and welfare: an empirical evaluation - Carreño, Nubia Stella; Hernández Escolar, Hugo Alfonso; Méndez Sayago, Jhon Alexander (Sociedad y Economía, 2011)
This article exposes the results of an academic research intended to estimate short run effects of microcredit on beneficiaries’ population at Bogota, Colombia. The evaluation is supported by propensity score technique and an asset index, designed under Principal Component Analysis. The different applied matching techniques (Kernel, nearest neighbor, radio and layer), at a α=5% significance level, show that the null hypothesis about positive effects absence on the asset index is rejected.